Podstawowe kategorie pojęciowe w ustawodastwie rolnym Polskiej Rzeczypospolitej Ludowej (próba usystematyzowania pojęć): [Basic categories of notions in agrarian legislation in the Polish People Republic] (Studia Prawnicze / The Legal Studies, 1985)
The categories of notions of agrarian legislation has been so far discussed in connection with individual legal solutions. There is no need to convince anybody that they are numerous and differenciated.In the 70s there was an attempt to take a broad view of agrarian legal problems but there have been no effects so far. A present attempt to define a complex of basic categories of notions in agrarian legislation refers to that trend. An attempt to specify and then systematize these categories has been limited to legal regulations concerning social and economic relations occuring in connection with organizing agricultural production units.Starting out from the constitutional regulation of agricultural problems the work distinguishes six basic categories of notions of agrarian legislation, namely: "agricultural output", "legal approach to land", "subjects entitled to purchase agricultural estates", "appropriate exploitation of farmland", "farm unit" and "person running a farm". The fact that agricultural output has been enumerated on the first place is very important as other categories of notions can be discussed only in connection with the first category. Functional connections between them allow to treat them as a system. The author shows a different from the traditional one approach to social and economic relations connected with organizing agricultural output and discusses some consequences of the new approach